AS A FACTOR OF EDUCATION- SOCIALIZATION (Academia Science Repository, 2023)
Young generation certain the goal in every way adult reach for social mind and behavior content to find directed activity is human in society certain providing qualities ( physical, spiritual, spiritual , intellectual ) on the way visible measures sum.